“A dynamic of blaming and counterblaming”: J.M. Coetzee’s Analysis of Self-deception in South African Resistance Literature - Niemi, Minna (Pivot: A Journal of Interdisciplinary Studies and Thought, 2011)
The aim of this article is to introduce briefly some of the more prominent aspects of these complex questions regarding the interplay of art and politics in the context of the South African literary discourse in the early 1980s. I explore South African resistance literature, and more particularly André Brink’s ideas, and his commitment to political struggle vis-à-vis Jean-Paul Sartre’s notion of politically committed art. I read Coetzee’s challenge to resistance literature as a response with striking similarities to Theodor Adorno’s criticism of committed art, which Adorno leveled at Sartre in his two-part essay “On Commitment.” As both Coetzee and Adorno demonstrate, committed art remains close to the power it criticizes, and does not break free from it. Coetzee maintains that it is the constant task of the writer to resist the binaristic logic of the state by avoiding the lure of self-deception and maintaining an awareness that he, too, is implicated by state violence.